The state of the banking sector of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
The article discusses the activities of commercial banks of Kazakhstan.Commercial Bank is currently the key element of the banking system. Theanalysis of the structure of total assets of banks, which showed that themajority of the assets of commercial banks related to the credit activity.The analysis of credit activities of commercial banks as a whole. Considersthe share of lending in the context of legal and physical persons. attentionto lending to small and medium enterprises, their share in total loanportfolio of banks. Lending affects the volume and structure of money supply,payment transactions, velocity of circulation of money stimulates thedevelopment of productive forces, and also contributes to the expansionof production and economic growth. Currently, according to banks, thecurrent level of credit risk in the loan portfolio is associated with a reductionin the creditworthiness of the borrowers and a decrease in consumerdemand. Restraint of banks in lending is also due to the low availability ofliquidity and high credit risk.